Slow and affective becoming-with in early childhood education as the initiation of cultivation - Nordström, Alexandra; Sintonen, Sara (Oslo University College, 2025)
In this paper, we explore slow and affective becoming-with in early educational contexts as the initiation of cultivation. A slow approach advocates varied pace and rhythm, diverging from goal-driven approaches. Affective intensities, including feelings, bodies, and sensory elements challenge Western understandings of child and childhood. Our starting point for this reconsideration is the Finnish scholar J.A. Hollo’s (1895-1967) educational thinking, emphasizing Bildung as a process and the initiation of cultivation. Exploring postqualitative and non-representational methodologies, we focus on the messy and mundane in-betweens in early childhood education. That is, altering how we perceive place by refocusing our gaze from a physical location to intricate, intertwining becoming-withs. By refocusing our gaze on the slow and affective here and now – by thinking, seeing, and feeling with Hollo – we aim to contribute to ongoing discussions on a post-developmental and post-neoliberal ECEC.